Garden events and artistic and anthropological partnerships with plants: Teresa Siewerdt in conversation with Joaquim Almeida - Almeida Neto, Joaquim Pereira de; Siewerdt, Teresa (Cadernos de Campo (São Paulo, 1991), 2023)
This text is a writing experiment mediated by plants. Its objective is to explore the possibilities of encounter between two disciplinary worlds that, despite being interested in a series of common themes and subjects, remain quite separate: the world of contemporary art and the world of anthropology. The text, which takes the form of a conversation, is guided by the presentation of four artistic works developed by Teresa Siewerdt between 2013 and 2019 and by a kind of root argument that seeks to undiscipline the recurring view of the garden and draw attention to the relationships established by plants and to what they can teach us.